Structural behaviour of precast lightweight foamed concrete sandwich panel (PLFP) with shear truss connectors - Goh, Wan Inn (2015)
Precast system is playing a very important role in industrialize building system to construct more affordable and quality houses to meet the high demands. Many researches have been carried out to develop precast sandwich wall panel with more benefits such as lighter in weight, environmental friendly and easy to construct compared to normal reinforced concrete panel. Therefore, a study was carried out to develop Precast Lightweight Foamed Concrete Sandwich Panel (PLFP) with shear truss connectors. The objectives of this study are to numerically investigate the PLFP panel with single and double shear truss connectors to determine its structural behaviour with validation from experimental work and to develop the empirical equation to predict its ultimate strength under axial load. PLFP panel is made of foamed concrete as the outer wythes which enclose a core layer of polystyrene. The wythes were reinforced with steel bars and tied to each other through the polystyrene layer by using steel shear connectors (bent at an angle of 45°). Experimental testing had been conducted to determine the material properties of foamed concrete and steel bar and used for PLFP model in finite element analysis. Eight half scaled PLFP panels were tested experimentally under axial load until it failed. Ultimate load carrying capacity, load lateral deflection profile, strain distributions and failure mode were recorded. Finite element analysis was carried out on PLFP panels which were validated with experimental results. Full scaled PLFP panels with single and double shear truss connectors had been studied numerically to investigate the effects of geometrical imperfection, slenderness ratio, thickness, and shear connectors toward its structural behaviour. From the results, it was found that when the rate of geometrical imperfection and slenderness ratio of PLFP panel increased, the ultimate load of PLFP panel decreased. The use of double shear truss connectors indicated improvement in the PFLP’s strength and stability under axial load and longitudinal shear force compared to single shear truss connectors. An empirical equation which was modified from previous research is proposed to predict the ultimate load carrying capacity of PLFP under axial load.